Actinopterygian fishes from the new Lower Permian locality of the Krkonose Piedmont Basin - Stamberg,S. (Journal of the Czech Geological Society, 2002)
Scales, bones and fragments of actinopterygians were collected from two horizons of grey, reddish, mauve and greenish laminated calcareous mudstones in an outcrop of the Prosecne Formation (Lower Permian) at Klasterska Lhota. Genera Paramblypterus, Amblypterus and Aeduella were distinguished among the new material. Several specimens of Aeduella represent the first described finds of this genus from the Permo-Carboniferous of the Bohemian Massif. Besides the maxilla, frontal, parictal, operculum, suboperculum and cleithrum, which are characteristic of Aeduella, also an isolated clavicle was described. The latter differs from the clavicle of Paramblypterus and Amblypterus and has been unknown till this time in Aeduella. A small, slender specimen close to Paramblyterus and Amblypterus but differing in some anatomical features is described separately as Type A.
Keywords: Actinopterygii; Lower Permian; Krkonose Piedmont Basin; Bohemia